Atropselective synthesis of N-aryl pyridones via dynamic kinetic resolution enabled by non-covalent interactions. Issue 12 (8th March 2022) - Sweet, Jamie S.; Wang, Ruichen; Manesiotis, Panagiotis; Dingwall, Paul; Knipe, Peter C.
Abstract : Hydrogen bonding in ortho -phenols enables enantioselective synthesis of axially chiral 2-pyridones via dynamic kinetic resolution. Abstract : The dynamic kinetic resolution of C–N atropisomeric pyridones was achieved via asymmetric phase-transfer catalysis, exploiting a rotational barrier-lowering hydrogen bond in the starting materials. X-ray and NMR experiments revealed the presence of a barrier-raising ground state CH⋯π interaction in the product, supported by DFT calculations. A co-crystal of the quinidine-derived phase-transfer catalyst and substrate reveals key substrate–catalyst non-covalent interactions.